Learn Salesforce Lightning The Visual Guide to the Lightning UI - Duarte, Felicia (Apress, 2018)
Refer to this invaluable how-to guide for basic training on Salesforce Lightning. Salespeople and technical users and consultants will no longer have to resort to learning the interface on their own, which is very time consuming. Learn Salesforce Lightning is a step-by-step visual guide that offers immediate and valuable solutions to the new set of UI tools included in Lightning. With chapters broken down into easily absorbed topics, you walk through the entire process of managing your daily activities within Salesforce, as well as basic customizations and system management. The book explains the primary use cases for Lighting, and simplifies some of the more complex features, such as opportunity stage management and the new dashboard builder. Topics covered include: Sales and service management Lightning Apps on the AppExchange Lightning dashboards and reports Lightning security Lightning Process Builder and more What You'll Learn: Navigate the Salesforce Lightning interface Know where to go in the setup area to make customizations Create dynamic reports and dashboards View Lightning on a mobile device Train other users on common day-to-day activities within Lightning.